Biological condition and population structure of benthopelagic shrimps in the Galicia Bank (NE Atlantic): Intra- and interspecific patterns. (February 2021) - Cartes, J.E.; Rodríguez-Ribas, R.; Papiol, V.; Valeiras, X.; Punzón, A.; Blanco, M.; Serrano, A.
Abstract: Few studies examined species or ecosystem dynamics on seamounts/banks. The Galicia Bank (GB), the deepest marine Special Area of Conservation in the Spanish Natura 2000 network, is considered a conservation priority because of its highly vulnerable habitats, such as cold-water and bamboo corals. The biological conditions and population structure of benthopelagic shrimps and their relationship with environmental conditions were analyzed during three expeditions over three years. Shrimps were collected by trawling. The gonadosomatic index (GSI) and nutritional condition (hepatosomatic index [HSI]) of shrimps were highest at the summit and deepest depths (>1500 m) sampled, whereas at intermediate depths between ca . 900–1500 m, these values were low. The intermediate depths around ca . 1000 m are influenced by the core of the Mediterranean Outflow Water (MOW), which is characterized by high salinity and low O2 concentrations. The highest GSI were recorded in species ( Aristeus antennatus, Plesionika martia ) distributed at summit, associated with higher Chl a 1–2 months before sampling at surface. The species with the highest HSI were also linked to Chl a 1–2 months and with higher %OM (generalized additive models, GAM, results). Overall, the studied shrimp species showed viable populations on GB, with reproductors/spawners more markedly distributed over the summit ( ca . <900 m). Notably, reproductors of several important commercial species ( A. antennatus, P. martia ) reached larger sizes and had greater potential fecundity (GSI) than in their optimal distribution areas, out of GB. P. martia recruitment only occurred in 2010, a year characterized by highly negative North Atlantic Oscillation (NAO) indices (−5.96/−5.2), suggesting that benthopelagic shrimps may colonize the GB at a variable periodicity as a probable consequence of the variable availability of zooplankton prey over seamounts. At the same time, species such as Aristaeopsis edwardsiana and P. martia may have some advantages when colonizing habitats in the GB because of the absence of competition from similar, even congeneric species. This was reflected in the patterns of size-depth distribution in the GB compared to mainland areas. In conclusion, the habitats of the GB and, by extension, of seamounts/banks contain rather isolated and small sub-populations, yet these populations can have a reservoir effect that can contribute to eventually restoring the main population core in other areas. Highlights: Important commercial shrimps inhabits the Galicia Bank (GB) with viable populations. The highest GSI and nutritional condition (HSI) recorded at summit of the Bank. Shrimps prefer more productive at bank summit and avoid less oxygenated waters when maturing and spawning. Plesionika martia recruitment took place on GB only in 2010, under highly negative NAO (−5, 96) conditions. GB is a reserve for subpopulations of benthopelagic shrimps that can restore exploited populations living out Seamounts.